Comparative study on spoilage and pathogenic bacteria in selected commercial marine and freshwater fishes - Chowdhury, Ahmed Jalal Khan; John, Akbar; M. S., Nurul Lyana; Nordin, Noor Faizul Hadry; Masseren, Noor Isma Yanti; Jaswir, Irwandi; Bulbul, Mahbuba (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Microorganisms are the major cause of spoilage of most seafood products. Fishes are more perishable than other protein foods and thus more prone to bacterial contamination. Based on above perspectives, a bacterial invasion in commercially important fresh and spoiled marine (Lates calcarifer, Lutjanus sanguineus) and freshwater fish (Pangasius pangasius) were analyzed using API 20E kit. Out of 25 isolates obtained from fresh water fish, only 6 isolates were characterized as Gram-positive bacteria and the rest were Gram negative strains (19 isolates). The most dominant genera were Vibrio, Enterobacter, Serratia, and Aeromonas. All these bacteria were found in both fresh fish and spoiled fish sample while Erwinia spp. and Kluyvera spp. were identified only in fresh fish samples. Out of four (4) strains of Staphylococcus spp., S. xylosus was detected exclusively from spoiled fish. The higher number of bacterial micro flora in the spoiled fish gut indirectly indicated increased microbial degradation in the fish gut during spoilage process. Notably, almost all the isolates were lactose degraders, positive oxidizers and carbohydrate fermenters. Vibrio fluvialis, Proteus mirabilis, Proteus vulgaris, Brucella sp. and Ochrabactrum anthropi were the human pathogenic bacteria found in marine fish Lates calcarifer (Sea perch). While Vibrio fluvialis, Proteus mirabilis and Proteus vulgaris were detected in Lutjanus sanguineus (Red snapper). The study portrays that the existing postharvest handling techniques could be a vital factor for degrading hygienic conditions of fish in local fish markets. Nevertheless, a long term monitoring is an urgently needed for sustaining the quality flesh of fish towards the betterment of the consumer’s health.